Social and psychological aspects of tax consulting in Ukraine - TKACHYK, Fedir (Scientific journal «World of Finance», 2019)
Introduction. Increase in the community understand the need for full and timely calculation and payment of taxes and duties and conscious understanding of their importance for the viability of the state, providing qualified and effective consultative assistance to taxpayers acting priority at the state tax consulting and corporate levels. An important role in this context is played by psychological traits taxpayers that understand key aspects of tax consulting. It increases the level of tax literacy and tax culture in society, strengthens economic competitiveness and creates a series of macroeconomic effects.The purpose of the article is the study of social and psychological aspects of functioning and improving tax consulting services in Ukraine.Results. The theoretical aspects of the tax consulting are investigated. The basic indicators of the State Fiscal Service of Ukraine in the field of consulting are analyzed. The psychological traits of the conduct of fiscal and tax advisors are systematized. Deals with the social component of the tax behavior of taxpayers and outlines the reasons prompting them to deviation. Showed the role and place of business taxation in the formation of tax culture. Proved, that the active outreach by SFS of Ukraine will increase the level of tax awareness and create a tax culture in society. Formation and development of the effective market of tax consulting in Ukraine will increase the level of service taxpayers at the corporate level will lead to optimization of fiscal policy and strengthen its social role.Conclusion. The ability to use the tax employees in the work of social and psychological technologies can increase the efficiency of their operations and create the basis for improving the confidence of taxpayers to the tax system in general, increase of tax culture in society, and to create a basis for the functioning of the corporate tax consultancy in Ukraine